2003
DOI: 10.1051/agro:2003020
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of oxalate ions and protons released by ectomycorrhizal fungi in rhizosphere soil

Abstract: -This paper deals with the study of proton and oxalate release by two ectomycorrhizal fungi, Hebeloma cylindrosporum and Rhizopogon roseolus, grown alone or in association with Pinus pinaster and supplied with nitrate. An original culture device made it possible to observe the growth of the ectomycorrhizal roots and to measure pH and oxalate content at different levels: roots, ectomycorrhizae, external hyphae and rhizosphere soil. The results showed differences between the two species grown in vitro. These dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
67
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(69 citation statements)
references
References 30 publications
1
67
0
1
Order By: Relevance
“…However, pine seedlings colonised by this species down-regulated LMWOA production compared to non-mycorrhizal seedlings (Van Schöll et al 2006a). Hebeloma cylindrosporum did not release oxalate Casarin et al 2003).…”
Section: Weathering By Rock-eating Ecm Fungi -A Further Element Of Ecmentioning
confidence: 79%
See 1 more Smart Citation
“…However, pine seedlings colonised by this species down-regulated LMWOA production compared to non-mycorrhizal seedlings (Van Schöll et al 2006a). Hebeloma cylindrosporum did not release oxalate Casarin et al 2003).…”
Section: Weathering By Rock-eating Ecm Fungi -A Further Element Of Ecmentioning
confidence: 79%
“…However, S. bovinus did not enhance weathering of muscovite and hornblende in the study by Van Schöll et al (2006b). Rhizopogon roseolus also produced large amounts of oxalic acid under a range of pH conditions (Ahonen et al 2000;Arvieu et al 2003;Casarin et al 2003). It also up-regulated oxalate exudation, compared to non-mycorrhizal seedlings, under conditions of Al toxicity (Van Schöll 2006).…”
Section: Weathering By Rock-eating Ecm Fungi -A Further Element Of Ecmentioning
confidence: 90%
“…Van Schöll et al (2006b) found that the ability of EMF in mineral weathering depended on the fungal species. Ability of EMF to acidify substrate varies with species (Casarin et al, 2003;Rosling et al, 2004) and mineral type (Rosling et al, 2004). EMF species also varies in organic ligand exudation (Casarin et al, 2003) and differs in their colonization ability (Dickie et al, 2002;Rosling et al, 2003).…”
Section: Emfmentioning
confidence: 99%
“…Interestingly, inter-and intraspecific differences in acidifying properties of oxalate-producing ectomycorrhizal species have been reported in vitro . However, in the study of Casarin et al (2003Casarin et al ( , 2004, only the acidifying ECM species R. roseolus and the poor oxalate producer ECM species H. cylindrosporum were used in association with Pinus pinaster plants grown in rhizoboxes containing a Mediterranean soil layer with a low level of easily available P. In these conditions, only R. roseolus hyphae were able to release oxalate into the soil that combined with calcium to form calcium oxalate (Casarin et al 2003). Oxalate release was accompanied by acidification and increase of Pi availability of rhizosphere soil (Casarin et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…We can hypothesise that it is Barber 1984) the NH 4 + ion per se which has an inhibitory effect on oxalate synthesis as organic nitrogen did not inhibit organic acid release in R. roseolus, contrary to ammonium (Plassard, unpublished data). When nitrate is supplied as the sole nitrogen source in the medium, the presence of calcium and bicarbonate ions was shown also to promote oxalate production in the fungus grown in pure culture (Lapeyrie et al 1987) or in association with the plant (Casarin et al 2003(Casarin et al , 2004.…”
Section: Introductionmentioning
confidence: 99%